Impact of cocoa rehabilitation programme on productivity and economic status of cocoa farmers in the Offinso District, Ghana - Boateng, Emelia Serwaa (University of Cape Coast, 2023)
The study sought to examine the impact of cocoa rehabilitation programme on the productivity and economic status of cocoa farmers of Offinso District in the Ashanti Region of Ghana. In this research, the descriptive research design was adopted with a sample size of 217 farmers using closed questionnaire. The study used both descriptive statistics and regression models in its analysis. the study concluded that 50.2 percent of the cocoa farmers, were between 10-20 years old. A further analysis revealed that 88.7 percent of the farmers make contact with agricultural extension officers for their services regarding their farms, 27.6 percent of cocoa farmers make contact with the agricultural extension officers for their services regarding their farms 3 times in a month, 74.10 percent of the cocoa farmers received other agricultural related training, 76.4 percent of the farmers were prepared to cut cocoa trees for complete rehabilitation. The study revealed that shaded agroforestry system, no shaded monocropping and cocoa Agronomists of the cocoa rehabilitation program helps to cultivate large scale, undertaking early intercropping, shade regulation, replanting in stages and selective replanting of trees to regulate cocoa crown’s shape and size. This was found to account for more than 43.3% of the level of output of cocoa production. The study revealed key challenges of the rehabilitation programme including inadequate credit facilities, unsatisfactory loan agreement conditions by creditors and unfamiliarity with modern methods of farming. The study made key recommendation. Key among this is that district agricultural extension offices should pay more visit to the cocoa farms to educate them more on modern methods of farming.
xii, 117p,; ill.
Keywords: cocoa; productivity and economic; farmers